Inovasi Aplikasi Sistem Data dan Layanan Sejahtera Bersama Bupati (SIDAYA SEHATI) dalam Optimalisasi Penyaluran Bantuan Sosial di Kabupaten Bangkalan - Royhan Hidayat; Eva Hany Fanida (Lembaga Pengembangan Kinerja Dosen, 2025)
In improving the quality of public services in the social sector, the Social Service Office of Bangkalan Regency introduced an innovation called the SIDAYA SEHATI Application (Prosperous Data and Service System with the Regent) to address various challenges related to the distribution of social assistance in the region. The study seeks to describe the SIDAYA SEHATI Application contributes to improving the effectiveness of social aid distribution, using a qualitative descriptive method with the analysis framework based on the innovation criteria outlined in Permen PAN-RB No. 91 of 2021, which includes 5 key aspects: having novelty, effectiveness, usefulness, ease of dissemination, and sustainability. Data were collected through observations, interviews, and documentation, then analyzed using the Miles and Huberman model. The results showed that the innovation of the SIDAYA SEHATI Application in optimizing the distribution of social assistance in Bangkalan Regency has met the criteria of having good novelty, but socialization still needs to be improved. Effective criteria have been achieved well, but the account verification process is still less effective. Useful criteria have been well realized, but the unavailability of password recovery options is still an obstacle for the community. The criterion of being easy to disseminate has been well realized, but server stability still needs to be addressed. Sustainable criteria have been well implemented, but unfortunately this innovation is still not available on the Play Store or App Store.